2016
DOI: 10.1159/000444544
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects in the Management of Cholestatic Liver Diseases

Abstract: Background: There is a great need for risk stratification in patients with chronic cholestatic diseases in order to allow for more personalized care and adapted management as well as for well-designed therapeutic trials. Novel tools for monitoring primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC) patients have been recently proposed. In addition, major insight has been gained into bile acid (BA) physiology during the last decade including the role of BAs as metabolic modulators and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The accumulation of hydrophobic bile acids is believed to induce chronic inflammation and hepatocyte apoptosis . Recent clinical studies indicate that disruption of intestinal barrier function and subsequent bacterial translocation also contribute to cholestatic liver disease progression, such as primary sclerosing cholangitis (PSC), primary biliary cholangitis (PBC), and noncholestatic liver diseases by inducing hepatic inflammation . It has been reported that PSC represents one of the most common extraintestinal manifestations of inflammatory bowel disease (IBD) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of hydrophobic bile acids is believed to induce chronic inflammation and hepatocyte apoptosis . Recent clinical studies indicate that disruption of intestinal barrier function and subsequent bacterial translocation also contribute to cholestatic liver disease progression, such as primary sclerosing cholangitis (PSC), primary biliary cholangitis (PBC), and noncholestatic liver diseases by inducing hepatic inflammation . It has been reported that PSC represents one of the most common extraintestinal manifestations of inflammatory bowel disease (IBD) .…”
mentioning
confidence: 99%
“…(3) It has been reported that PSC represents one of the most common extraintestinal manifestations of inflammatory bowel disease (IBD). (3) The close association between PSC and IBD highlights the importance of the gut-liver axis. (4) Furthermore, disruption of the intestinal barrier was not only observed in obstructive jaundice patients, but also in bile duct ligation (BDL) rodent models of cholestatic liver diseases.…”
mentioning
confidence: 99%
“…A high concentration of bile acids, especially the hydrophobic bile acids, is particularly toxic and promotes hepatocyte damage, liver fibrosis, cirrhosis and hepatocellular carcinoma under cholestatic conditions (29,30). Notably, the reduced flow of bile acids into the small intestine facilitates the movement of flora and bacterial endotoxins from the portal vein into the liver and causes disruption of the intestinal epithelial barrier (31)(32)(33). Our previous study found that chronic liver injury patients also displayed intestinal barrier dysfunction, manifesting as significantly elevated serum endotoxin, DAO and D-Lac compared with normal controls (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Obeticholic acid (OCA) is a novel farnesoid X receptor agonist that has been recently FDA-approved for treatment of PBC. [89][90][91][92][93] OCA (at a dose of 10 or 5 mg titrated to 10 mg/d) induced 35% reduction in ALP from baseline, normal bilirubin level and improvements in GGT, ALT and AST after 12 months of therapy. Patients who failed to achieve these endpoints had significantly increased risk for LT and death compared to patients who achieved those endpoints (HR 2.83, P < .001).…”
Section: Pharmacological and Surgical Treatmentmentioning
confidence: 99%
“…Experts recommend starting with full dose UDCA (13‐15 mg/kg/d) in 2‐4 divided doses (with food); in patients who are intolerant of the full weight‐based dose, the dose can be lowered and/or tapered up over a period of 1‐2 weeks. Obeticholic acid (OCA) is a novel farnesoid X receptor agonist that has been recently FDA‐approved for treatment of PBC . OCA (at a dose of 10 or 5 mg titrated to 10 mg/d) induced 35% reduction in ALP from baseline, normal bilirubin level and improvements in GGT, ALT and AST after 12 months of therapy.…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%